Functional effects of drugs and toxins interacting with NaV1.4 - Zou, Xinyi; Zhang, Zixuan; Lu, Hui; Zhao, Wei; Pan, Lanying; Chen, Yuan (Frontiers in Pharmacology, 2024)
NaV1.4 is a voltage-gated sodium channel subtype that is predominantly expressed in skeletal muscle cells. It is essential for producing action potentials and stimulating muscle contraction, and mutations in NaV1.4 can cause various muscle disorders. The discovery of the cryo-EM structure of NaV1.4 in complex with β1 has opened new possibilities for designing drugs and toxins that target NaV1.4. In this review, we summarize the current understanding of channelopathies, the binding sites and functions of chemicals including medicine and toxins that interact with NaV1.4. These substances could be considered novel candidate compounds or tools to develop more potent and selective drugs targeting NaV1.4. Therefore, studying NaV1.4 pharmacology is both theoretically and practically meaningful.